Financial Statements in the Public Sector of the Republic of Bulgaria under the conditions of European Integration - Radka Andasarova; Daniela Feschiyan (Икономика и компютърни науки)
The aim of this study is to analyze financial statements in the public sector of the Republic of Bulgaria within the context of European integration focusing on the International Public Sector Accounting Standards (IPSAS) and the European System of Accounts (ESA 2010). The interrelation between the frameworks of financial and statistical reporting is examined on theoretical grounds. The study explores the main uses of financial information: on the one hand – for facilitating the processes of financially justified decision-making and assuming management accountability to the interest parties, and on the other hand – for the purposes of macroeconomic analysis and presentation of key macroeconomic indicators. The detailed review on the applicability of the specified reporting frameworks highlights various challenges that should be considered when defining measures on improvement of the regulatory framework in the field of the public sector financial reporting in Bulgaria, in favour of, and for the best interests of the users of general-purpose financial statements